Motor function, quality of life, and prevalence among children in a cerebral palsy community - Mona Oktarina; Andy Sirada; Rycco Darmareja; Ghyffara Agathy Putri; Fadhira Citra Surya Anjani; Solagracia Sukatno Putri (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Cerebral palsy (CP) is the most common motor disability in children. It often causes motor impairments that reduce functional independence and participation, particularly in countries like Indonesia and low- and middle-income countries. The aim of this study was to assess motor function, quality of life, and prevalence of CP in a community-based population. Methods: A cross-sectional descriptive study was conducted on 80 children with CP from a community in Jakarta aged 5–18 years. They were selected through purposive sampling. All participants had a confirmed diagnosis of CP and consent from their parents or guardians. Children with other physical disabilities or who were unable to communicate were excluded. The Gross Motor Function Classification System (GMFCS) was used to assess motor function, and the Cerebral Palsy Module of the Pediatric Quality of Life Inventory (PedsQL) 3.0 was used to measure quality of life. Results: A total of 83.8% of participants were adolescents aged 13–18 years with spastic CP. With 46.3% at GMFCS level IV and 28.7% at level V, severe motor impairments were common, but 61.3% of children reported a good quality of life. Motor function and quality of life were positively and significantly correlated (r = 0.345, p = 0.002). Conclusion: The motor function of children with CP is strongly associated with their quality of life. This suggests that comprehensive and ongoing rehabilitation is necessary to improve functional participation and overall well-being.